Various macro and micro-morphological characters of three sex types of highland papaya (Vasconcellea pubescens) in Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Laily AN, Daryono BS, Purwantoro A, Purnomo. 2022. Various macro and micro-morphological characters of three sex types of highland papaya (Vasconcellea pubescens) in Java, Indonesia. Biodiversitas 23: 6238-6246. Highland papaya (Vasconcellea pubescens A.DC.), locally called karika, is a fruit plant successfully introduced to Java, Indonesia. V. pubescens plays an essential role as it contains various substances that can be used as ingredients in the food, pharmaceutical, and cosmetic industries. This plant is dioecious and monoecious as it contains three sex types, namely female, male, and monoecious. It grew from seed and began to bear fruit two years after sowing. The consumer preference for fruit is produced from female plants because female plants produce fruit faster, more abundantly, and with maximum fruit size under suitable environmental conditions. Sex differentiation is important for farmers to ensure the growth of female plants. Therefore, this research aimed to investigate the variation in macro and micro-morphological characters. The results showed that leaf and flower differ in macromorphological characters among the three sex types. Similarly, there were considerable differences in the trichomes of female and monoecious plants based on micro-morphological characteristics. There was no significant difference in seed shape between those. Seeds from female and monoecious plants differed in macro and micro-morphological characters. Macro and micro-morphological characters might have potential applications in early sex determination in V. pubescens. Macro and micro-morphological characters have many potential applications in early sex determination in V. pubescens.